EMO DEMO EDUCATION ON IMPROVING MATERNAL KNOWLEDGE - Ulva Larissa; Riris Diana Rachmayanti (Universitas Airlangga, 2022)
Introduction: Breast milk is food that is first given to babies after birth, given naturally by the mother through the process of breastfeeding. Breast milk has many nutritional contents such as minerals and vitamins that will be needed by newborns. The WHO says that, every year, 800,000 children’s lives can be saved with breast milk. In East Java Province the exclusive breastfeeding in 2018 was 77.51%, whereas in the city of Surabaya, the achievement of exclusive breastfeeding in 2018 only reached 71.62%. At the location of the study of 85 mothers with the baby, only 3 people provided exclusive breastfeeding. Supplementary breastfeeding before six months of age is one of the reasons for the low coverage of exclusive breastfeeding in Indonesia. The emo demo is a health education that uses an interactive demonstration to add insight and knowledge. The purpose of this paper is to determine the differences in maternal knowledge in the pre-test and post-test about exclusive breastfeeding and the provision of MP-ASI. Methods: This study uses quantitative research with the One Group Experiment Pre-Test Post-Test approach. This research was conducted in the working area of ​​the Sawah Pulo Puskesmas, precisely at Baduta mothers in the RW IX area of ​​Kelurahan Ujung with a population of 85 people and a total sample of 20 people. Conclusion: The sampling technique in this study is random sampling. The average knowledge of mothers about Exclusive ASI and MP-ASI has increased after being given education according to the Wilcoxon test results.